Computation of Topological Indices of Graphene. (18th August 2015) - Sridhara, G.; Rajesh Kanna, M. R.; Indumathi, R. S.
Abstract : We compute ABC index, ABC4 index, Randic connectivity index, Sum connectivity index, GA index, and GA5 index of Graphene.